Behavioral changes induced through adenosine A2A receptor ligands in a rat depression model induced by olfactory bulbectomy. Issue 5 (17th April 2018) - Padilla, Karla Margarita; Quintanar‐Setephano, Andres; López‐Vallejo, Fabian; Berumen, Laura Cristina; Miledi, Ricardo; García‐Alcocer, Guadalupe
Abstract: Background: Major depressive disorders are characterized by their severity and long‐lasting symptoms, which make such disorders highly disabling illnesses. Unfortunately, 50% of major depressive patients experience relapses, perhaps partly because drug research has been performed only in animal models that screen for antidepressant drugs that appear to only ameliorate acute depression symptoms. The bilateral olfactory bulbectomy (OBX) animal model presents the advantage of mimicking the symptoms of chronic depression by means of brain surgery. Adenosine purinergic receptors A2A (A2AR) have been the target of interest in the field of psychiatric diseases. This study aimed to show which A2A receptor ligands exert antidepressive‐like effects in the OBX rat model. Methods: Forty Sprague‐Dawley male rats were divided into four groups: control, OBX + vehicle, OBX + ZM 241385, and OBX + adenosine groups. Pharmacological treatment was administered for 14 days, and the rats were examined via the forced swim test (FST), open field test (OFT), and sucrose preference test (SPT). Results: The OBX + ZM 241385 group exhibited decreased immobility time in the FST, decreased isolation time in the OFT, and reversed anhedonia behavior in the SPT compared to the vehicle group. However, no significant differences for adenosine treatment were found. Conclusions: ZM 241385 administration (2 mg/kg i.p.) restored behavioral changes associated with OBX‐induced depression. Abstract : Antidepressant activity of A2A receptor agonist and antagonist chronic administration was evaluated in OBX model. ZM 241385 (2 mg/kg i.p) administration during two weeks of reversed depressive behaviors induced by OBX surgery. In silico studies showed that ZM 241385 could exert agonist as well as antagonist bound interactions with the A2A receptor